In the name of my parents: Entrepreneurship and the intergenerational transmission of values - Michael Wyrwich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Mounting empirical evidence shows that kids of self-employed parents are very likely to become entrepreneurs themselves. These findings are often attributed to the intergenerational transmission of parental norms and values. However, many papers in the field are not that explicit about parental values. Furthermore, nearly all studies neglect potential heterogeneity of entrepreneurial parents and their values. I argue that values of entrepreneurial parents can be quite different due to context factors like their motivation for being self-employed (e.g., necessity- vs. opportunity driven). I also think that direct information on values should be exploited to understand their intergenerational transmission. To this end, I fill research gaps and contribute to the literature by making use of a natural experiment. This allows identifying a group of entrepreneurial parents with a distinct value orientation and detecting a transmission of these parental values.
Keywords: L26; J13; J62; P37; Z13; 330; entrepreneurship; intergenerational transmission; values